International Contagion Effects from the Russian Crisis and the LTCM Near-Collapse - Fry, Renee (IMF Working Papers; Working Paper ;, 2002)
We examine empirically the episode of extraordinary turbulence in global financial markets during 1998. The analysis focuses on the market assessment of credit risk captured by daily movements in bond spreads for twelve countries. A dynamic latent factor model is estimated using indirect inference to quantify the effects of unanticipated shocks across borders or "contagion," controlling for common global shocks, country-specific shocks and regional factors. The results show that there were substantial international contagion effects resulting from both the Russian and LTCM crises. The proportion of volatility explained by contagion is not necessarily larger in developing than in developed nations.